Earthquake terror - Kehret Peg 1936-; Peg Kehret (New York : Scholastic, 2011)
When an earthquake hits the isolated island in northern California where his family had been camping, twelve-year-old Jonathan Palmer must find a way to keep himself, his partially paralyzed younger sister, and their dog alive until help arrives.
M
690